2016
DOI: 10.1186/s40562-016-0036-5
|View full text |Cite
|
Sign up to set email alerts
|

A new parameter of geomagnetic storms for the severity of space weather

Abstract: Using the continuous Dst data available since 1957 and H component data for the Carrington space weather event of 1859, the paper shows that the mean value of Dst during the main phase of geomagnetic storms, called mean Dst MP , is a unique parameter that can indicate the severity of space weather. All storms having high mean Dst MP (≤−250 nT), which corresponds to high amount of energy input in the magnetosphere-ionosphere system in short duration, are found associated with severe space weather events that ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 14 publications
0
24
0
Order By: Relevance
“…The storm sudden commencement took place at around 0445 UT followed by a long MP lasting until 2300 UT. It has an intensity (or minimum Dst or DstMin) of −223 nT and impulse strength (or mean Dst during MP; Balan et al, ) of −113 nT. During the MP, the Brazilian sector (LT = UT − 3) was on the dayside and facilitated to investigate the storm time response of equatorial dynamics and distinct features like the F 3 layer.…”
Section: Resultsmentioning
confidence: 99%
“…The storm sudden commencement took place at around 0445 UT followed by a long MP lasting until 2300 UT. It has an intensity (or minimum Dst or DstMin) of −223 nT and impulse strength (or mean Dst during MP; Balan et al, ) of −113 nT. During the MP, the Brazilian sector (LT = UT − 3) was on the dayside and facilitated to investigate the storm time response of equatorial dynamics and distinct features like the F 3 layer.…”
Section: Resultsmentioning
confidence: 99%
“…However, while studying what determines the severity of the space weather, we realized that the storm intensity (DstMin) is insufficient to distinguish between the severe space weather (SvSW) causing electric power outages and telegraph system failures and normal space weather not causing such severe effects (Balan et al, 2014). Our studies also showed that the mean value of Dst during MP (⟨Dst MP ⟩) can indicate the severity of space weather (Balan et al, 2016). It can also be used as a better reference than DstMin in developing a scheme for forecasting SvSW using ICME velocity V and IMF Bz (Balan, Ebihara, et al, 2017).…”
Section: Introductionmentioning
confidence: 85%
“…It represents the impulsive strength (or strength in short) of Dst storms while DstMin represents their intensity (Balan et al 2014). It (⟨Dst MP ⟩) has been shown to be a unique parameter that can indicate the severity of space weather while the conventional parameter DstMin is insufficient (Balan et al 2016). Average DstMin (=ΣDstMin/number of storms) and average ⟨Dst MP ⟩ = (Σ⟨Dst MP ⟩/number of storms) represent the average intensity and average strength of a certain number of storms during a specific period.…”
Section: Storm Analysismentioning
confidence: 99%